2021
DOI: 10.1039/d1ra07713a
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic copper-promoted oxidative dehydrosulfurative carbon–oxygen cross-coupling of 3,4-dihydropyrimidine-1H-2-thiones with alcohols

Abstract: A wide range of readily available DHPMs and alcohols makes the presented reaction an attractive method to access biologically valuable 2-alkoxypyrimidine derivatives with rapid diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As described in previous reports regarding the oxidative dehydrogenation (aromatization) and the oxidative dehydrosulfurative cross-coupling reactions of DHPM derivatives possessing the C4 t -Bu group, published by others and us, these results support the involvement of a radical intermediate in the aromatization process. 16,19,29,30 When the reaction of 2-mercaptopyrimidine 1s with aniline was performed, the desired pyrimidine 5b (ref. 31) was obtained (Scheme 4b), consistent with the proposition that the C–S single bond generated after deprotonation is involved in the reaction of DHPM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As described in previous reports regarding the oxidative dehydrogenation (aromatization) and the oxidative dehydrosulfurative cross-coupling reactions of DHPM derivatives possessing the C4 t -Bu group, published by others and us, these results support the involvement of a radical intermediate in the aromatization process. 16,19,29,30 When the reaction of 2-mercaptopyrimidine 1s with aniline was performed, the desired pyrimidine 5b (ref. 31) was obtained (Scheme 4b), consistent with the proposition that the C–S single bond generated after deprotonation is involved in the reaction of DHPM.…”
mentioning
confidence: 99%
“… 15 Recently, we developed Cu-promoted C–O cross-coupling of DHPM with boric ester (borate) or alcohol accompanying concomitant oxidative dehydrogenation (aromatization) to produce 2-alkoxypyrimidines ( Scheme 1c ). 16 Albeit large amounts of Cu (4.5 equivalents) as in the case of the Liebeskind–Srogl-type oxidative dehydrosulfurative C–N cross-coupling, the results demonstrated that the thiono substrate is a suitable electrophilic partner for Cu-promoted C–O cross-coupling, which inspired us to explore Cu-promoted oxidative dehydrosulfurative C–N cross-coupling of DHPM with amine to provide 2-aminopyrimidine compounds ( Scheme 1d ). As a surrogate for the 2-(pseudo)halopyrimidines, DHPMs bearing various C4–C6 substituents can be readily produced by the Biginelli three component reaction with versatile aldehyde, β-ketoester, and thiourea.…”
mentioning
confidence: 99%